Clichés and common wording in the letters of guarantee - Elena A. Kuvshinova, Galina N. Pudikova, (Opción, 2019)
The article deals with the features of Russian and English formal writing through the example of guarantee letters, given the trade growth in Russia and the English-speaking countries via a comprehensive study of theoretical, methodological and practical approaches to the content analysis of documents related to business practice. As a result, special word combinations are constantly reproduced in a ready-made form, are unchangeable and may be regarded as idiomatic expressions by function. In conclusion, Russian and English writing styles are somewhat similar due to similar normative approaches used when writing guarantee letters both in Russian-speaking and English-speaking countries